Enacting Deliberative Governance in Innovation of Labour Protection Policy (Case Study in Banyumas District, Central Java) - Tasroh, Tasroh; Setyoko, Paulus Israwan (Magister Ilmu Administrasi Publik, 2025)
This study aims to enact labor protection policy deliberations as an alternative policy innovation. By using qualitative descriptive research methods and observations of various models of labor protection policy deliberation in Banyumas Regency and a study of labor protection policy documents in the period 2021-2024, with in-depth interviews with 50 key informants, it can be concluded that two models of policy deliberation are founded. They are an elite model held by executive and legislative actors; the other is called private one handled by labour and corporate organization actors. The two models finally unified to improve the labor protection policy design process, encourage the formation of various public discussions and debates, and encourage the authentic participation of citizens, corporations, and workers. By blending them, the degree of consensus and collaboration across interests autonomously develops their potential and authority to jointly realize the target of social security participation programs. However, there are still various obstacles, including the limited budget and minimal awareness of elite actors. It is recognized that the development of more democratic labor policy deliberations shows a positive trend for regional governments in the future as the new capital for regional development. Because of the wider involvement, participation, availability of legitimate public space and wider collaboration have been proven to significantly improve the quality of labor protection policies at a local level. However, supervision and policy guidance must be carried out by all actors to improve the welfare of workers as a whole.